FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA UNTUK MEMILIKI REKENING TABUNGAN BRI - Br Gintingting, Sinthya Angelica; Simanullang, Paken Taras; Siallagan, Hamonangan (Jurnal Daya Saing, 2025)
Abstract The economic business is growing along with technological advances. The banking sector is no exception, all economic activities are not limited to location and time. Currently, almost all economic activities depend on banking services such as financing and storage. In fact, it is noted that the need for funds continues to increase, leading to the establishment of more financial institutions, both banks and non-banks, both government and private. Currently, people from various professions must have used banking services either in the form of financing or investment or storage. The daily lives of students are greatly assisted by financial institution products.This study is expected to provide a deeper understanding of students' financial behavior, as well as the factors that influence their decisions in opening savings accounts. The results of this study are expected to be used by educational institutions, banking institutions, and the government to design financial education programs and policies that support the improvement of financial literacy among students. .